Ser y no estar. Esa es la cuestión de la física cuántica - C. De la Torre (Revista de Enseñanza de la Física, 2016)
Quantum mechanics and relativity force drastic modifications in our concepts of space and time. Relativity introduces "proper" space-time and quantum mechanics modifity concept of focalization.